Efficiency or Profitability? Strategic Dilemmas of Islamic Banks in the Global Financial Landscape - Ian Alfian; Surya Agustina; Saparuddin Siregar; Sugianto (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Purpose: This study aims to systematically analyze the relationship between efficiency and profitability in Islamic banks amid global financial dynamics shaped by crises, the COVID-19 pandemic, accelerated digitalization, and sustainability pressures. The research highlights a strategic dilemma faced by Islamic banks regarding whether to prioritize operational efficiency for long-term sustainability or emphasize short-term profitability, especially within the context of Sharia-based financial intermediation. Method: A Systematic Literature Review (SLR) approach was employed by synthesizing 30 international Scopus-indexed articles published between 2019 and 2025. The selected studies encompass analyses of internal banking determinants, comparative frameworks between Islamic and conventional banks, and contextual assessments involving regulatory, technological, and macroeconomic factors. Results: The synthesis confirms that profitability in Islamic banks is strongly associated with internal factors such as capital strength, liquidity management, asset quality, and governance mechanisms. However, efficiency emerges as a critical determinant of long-term sustainability, particularly under conditions of heightened competition and limited financial instruments within Sharia-compliant frameworks. Comparative analyses reveal a unique trade-off for Islamic banks driven by Sharia compliance constraints, resulting in distinct efficiency-profitability dynamics compared to conventional banking models. Implication: The findings underscore the necessity for Islamic banks to redesign strategic orientations by integrating digitalization, fintech-based innovations, and sustainable finance mechanisms to balance efficiency and profitability in a competitive global environment. From a policy perspective, the study informs regulators and industry stakeholders regarding the structural reforms required to enhance Islamic banks' competitiveness and resilience. Originality: This research contributes to the literature by synthesizing the most recent empirical and conceptual studies on Islamic bank performance and by elucidating the specific trade-offs between efficiency and profitability. The article offers a contemporary perspective on strategic repositioning within the Islamic banking sector and proposes a conceptual foundation for future empirical model development.